Dredged sediments as a resource for brick production: Possibilities and barriers from a consumers' perspective. (April 2015) - Cappuyns, Valérie; Deweirt, Valentine; Rousseau, Sandra
Highlights: Consumers are suspicious towards bricks produced from dredged sediments. Technical quality, safety and environmental impacts are considered key characteristics. Public has insufficient knowledge on bricks produced from dredged sediments. Sensitization and provision of information to customers are of primary importance. Abstract: A possible solution for the oversupply of dredged sediments is their use as a raw material in brick production. Despite the fact that several examples (e.g., Agostini et al., 2007; Hamer and Karius, 2002; Xu et al., 2014) show that this application is feasible, some economic, technical and social limitations interfere with the development of a market of dredged materials in brick production in Flanders. While we describe the main characteristics of the supply side, we focus on the limitations and barriers from the demand side in the present study. Based on a consumers survey we analyze consumers' risk perceptions and attitudes towards bricks produced from dredged sediments. Consumers in Flanders are rather suspicious with respect to bricks produced from dredged sediments and their risk perception is mainly determined by the possibility of a bad bargain (brick of inferior quality) and the connotation with chemical contamination. The willingness to pay for bricks made from dredged sediments is mainly influenced by the age of the respondents, as well environmental awareness, and the respondents' belief in their ability to influence environmental problems. Sensitization and information of customers seems to be of primary importance to make dredged-sediment-derived bricks a successful product.